Product differentiation: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
The way products can secure premium prices through differentiation strategies has expanded consistently in recent decades. Besides the traditional strategies linked to product branding, product differentiation based on perceived ‘quality’ attributes is emerging as an important means of market repositioning for ACP producers. This Executive Brief examines the 2012-13 developments in the main product differentiation market components, such as geographical indications (GIs), organic, fair trade and sustainability product markets, and other quality-based differentiation initiatives. Special attention is given to the EU policy debates and trends and the implications for ACP countries, who will have to set up strategies for staying on top of all these developments in order to capture the opportunities of price premiums that can be generated.